EVALUASI SISTEM DISTRIBUSI DESA KAMARORA KECAMATAN NOKILALAKI KABUPATEN SIGI - Franky Tatundang; Mohammad Arwan; Muhammad Sarjan; Yulius S. Pirade (Foristek, 2019)
The development of technology from year to year is greatly improved, many supporting needs must be prepared specifically for electrical energy needs. The side ofthe distribution of electricity and its utilization must meet the requirements so that in its use can be more optimal and does not cause harm and accidents for humans and loss of property. Kamarora is one of the villages that also uses and utilizes electricity resources in Nokilalaki district. The village has 1 unit of 100 kVA capacity portal type transformer. In this study used measurement methods, customer data collection, and checking directly on the connection in each phase to find out the percentage of transformer loading performance and minimize unbalance of the load transformer. The results of research and analysis, the distribution transformer in Kamarora village have the highest loading conditions with peak load times (PLT) line 1 and 2 at 19:00 pm with a loading percentage value of 60.47 %, the value of imposing a transformer means that it is still underloaded. And then, the unbalance of the load transformer is high enough, the total power used in line 1is phase R (3600 VA), S (9400 VA), T (17400 VA). Line 2 westward is phase R (16150 VA), S (18900 VA), T (21950 VA) and line 2 eastward is phase R (17050 VA), S (18850 VA), T (3850 VA). Planning the load distribution for each line 1 and 2, namely in the line of 1is phase R (10200 VA), S (9400 VA), T (10800 VA).Line 2 westward is phase R (19250 VA), S (18900 VA), T (18850 VA) and line 2 eastward is phase R (23841 VA), S (23844 VA), T (24188 VA).